PENGARUH PUPUK ORGANIK DALAM MENGEFISENKAN PUPUK NITROGEN UNTUK PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Wulandari, Windri '; ', Idwar '; ', Murniati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of research was to know the effect of organic fertilizers in efficiency addition of nitrogene, organic fertilizers and nitrogene fertilizers, and for to obtain growth and yield of onion (Allium ascalonicum L.) was good with high efficiency. The research has been conducted in the area of Agricultural Extension Hall, the village of Sungai Geringging, subdistric Kampar Kiri, Regency of Kampar, Riau Province. This research conducted in 4x2 factorial experiment, arranged in a Randomized Block Design (RAK). The first factor is organic fertilizer itc, without organic fertilizer, animal manure 25 ton/ha, the rice straw compost fertilizer 31,25 ton/ha, green manure 10 ton/ha. The second factor the source of nitrogene itc urea 543 kg/ha, ZA 1190 kg/ha. The observed parameters include the total of leaves, plant dry weight, N uptake efficiency, total tuber, convolution tuber, fresh weight tuber, weight shelf of tuber, the effect of organic fertilizer on the efficiency of nitrogene production. The results of research, showed treatment green fertilizer and urea fertilizer produced the highest yield on the observation weight shelf of tuber is 2,60 kg/ plot. Keywords: onion, organic fertilizers and nitrogen fertilizers.